Corporate Governance and Private Capital Flows to Latin America - Alberto Chong; Alejandro Izquierdo; Alejandro Micco; Ugo Panizza (Inter-American Development Bank, Research Department, 2003)
According to recent research, external factors and political governance considerations are key determinants of capital flows in Latin America. We postulate that corporate governance is a crucial determinant as well. We show that while the region is characterized by relatively low levels of corporate governance it shows highly volatile capital flows. The high level of economic volatility that characterizes the region is partly due to the behavior of capital flows which, in turn, are influenced by external factors. The paper shows that by implementing better corporate governance the region could reduce the sensitivity of capital flows to external shocks and hence reduce the volatility of its economy.
Keywords: 330; Corporate Governance; Auslandsinvestition; Kapitalmobilität; Lateinamerika